Peran Orangutan Information Centre Dalam Konservasi Orangutan Di Taman Nasional Gunung Leuser Melalui Collaborative Management Plan-Small Grants Programme - Athalla Vareel Ebsyar; Zulkifli Harza; Putiviola Elian Nasir (Andalas Institute of International Studies, 2023)
The habitat of the Sumatran orangutan in the Gunung Leuser National Park (GLNP) area is under threat, due to illegal logging activities, construction of facilities and infrastructure, and encroachment on boundaries. In an effort to overcome this problem, the ASEAN Centre for Biodiversity (ACB) in collaboration with the Kreditanstalt fur Wiederaufbau (Kfw) created the Small Grants Program (SGP). SGP aims to support the efforts of the ASEAN Heritage Park (AHP) in protecting biodiversity, one of which is the orangutan. TNGL as AHP has been selected to run SGP in Indonesia and the Orangutan Information Centre (OIC) has been selected as a partner to run the SGP cycle one and cycle two at TNGL. OIC as a non-governmental organization (NGO) is taking part in orangutan conservation efforts in Gunung Leuser National Park through the Small Grants Program of the ASEAN Centre for Biodiversity. The research method used is qualitative using descriptive analysis research types and utilizing interview data with the Orangutan Information Center and observations of the Gunung Leuser National Park. The concept of the role of non-governmental organizations according to Lewis and Kanji is used to answer the research problem formulation. In the SGP ACB project, OIC plays the role of implementer by carrying out activities, namely restoring the Induk Barak area, compiling technical guidelines for orangutan protection and mitigation strategies on the Karo Langkat road, conducting surveys of orangutan population density on the Karo Langkat road and Halaban restoration. As a catalyst OIC carried out activities namely facilitating restoration training for the Barak Induk community group, advocating for the government for the protection and mitigation of orangutans on the Karo Langkat road, conducting permaculture activities in (Halaban village, Telagah village and Bukit Mas village). As a partnership, OIC carries out activities, namely working with the Barak Induk community to restore the Barak Induk area, working with the government to conduct a population density survey of orangutans on the Karo Langkat and Halaban roads.